The Effect of Telerehabilitation on Missed Appointment Rates - Lyn T. Covert; John T. Slevin; Jessica Hatterman (International Journal of Telerehabilitation)
The purpose of this study was to examine the effect of telerehabilitation on missed appointment rates in a rehabilitation clinic.  Clients fail to attend scheduled appointments for a variety of reasons.  Unmet appointments represent a loss of financial support as well as diminished efficiency and capacity to provide services. Speech therapy utilizing multiple appointments is most difficult to maintain during a treatment regimen. This may cause individuals to miss appointments and therefore not achieve desired results.  For this study, researchers utilized an intense speech therapy technique, the Lee Silverman Voice Treatment (LSVT®) to measure compliance with scheduled appointments. Participants were randomized to either in-person treatment or telerehabilitation treatment at a site distant from the speech-language pathologist. Participants in the telerehabilitation (TR) condition completed significantly more appointments than participants in the in-person (IP) condition. When comparing results of treatment for each condition, there were no significant differences in outcome whether treated in the IP or TR condition of the study for monologue and picture description tasks, which are closely associated with conversational speech.  There was a difference in the reading task with participants demonstrating significantly better post treatment results in the IP condition.  The reason for this disparity is unclear and warrants further study.